Pelatihan Manajemen Biaya dan Laporan Keuangan Sederhana: Studi Kasus Peternak Ayam di Desa Gandaria: Training on Cost Management and Simple Financial Reporting: A Case Study of a Poultry Farmer in Gandaria Village - Fattah, Tino Kemal; Pebriadi, Muhammad Syahid; Amelia, Rizky; Salman, Putriana (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Poultry farming plays a crucial role in supporting rural community welfare; however, many farmers face challenges in financial record-keeping and cost management, which hampers their ability to assess profitability. This community service program aimed to enhance the knowledge and skills of poultry farmers in Gandaria Village in managing costs and preparing simple financial reports. The program was conducted in several stages: preparation, pre-test, material delivery, mentoring, post-test, and financial reporting. Methods included collecting baseline financial data, providing interactive training on identifying fixed and variable costs, budgeting, systematic financial recording, and applying income statements as evaluation tools. The results indicated an improvement in the farmers' understanding, as reflected in their ability to prepare a simple financial report that accurately illustrates the real financial condition of the poultry business. The post-test showed that the farmer could identify cost components, calculate revenues, and compile an income statement, although the report still indicated a loss due to inefficient feed management. The primary outputs of this program were a straightforward income statement and a financial reporting template, designed for continuous use in future recording and evaluation. Overall, the program demonstrates that structured training and mentoring can enhance financial literacy, provide practical tools for monitoring profitability, and support better decision-making, thereby contributing to the sustainability of poultry farming in Gandaria Village.